FINANCIAL INSTRUMENTS IN THE DEVELOPMENT OF BUSINESS INNOVATIONS - Yankovoi, Roman; Sembiyeva, Lyazzat (Socio-economic relations in the digital society, 2023)
This article analyzes the role of financial instruments in supporting and stimulating business innovations, considers venture financing, lending, crowdfunding and other mechanisms as key levers for the development of innovative projects and startups. The purpose of the study is to identify and analyze the factors that make certain financial instruments more effective in supporting innovation. The advantages and disadvantages of each instrument are considered, and their ability to adapt to the changing business environment is discussed. The article utilizes a variety of research methods, including literature review, case studies, and comparative analysis, to provide a comprehensive view of the topic. The study shows that venture capital investments often provide not only capital, but also valuable knowledge, mentoring, and access to a network of contacts. The results indicate that traditional bank lending is often inaccessible or insufficiently flexible for innovation-oriented companies due to the high level of risk. However, specialized loan programs, such as government guarantees and subsidized loans, can increase the availability of credit for innovative projects. Crowdfunding is an effective tool for validating market demand and raising initial funding, especially for projects that go beyond traditional investment models. The results emphasize the importance of financial innovations, such as fintech solutions and digital currencies, which can simplify access to capital and reduce transaction costs for innovative enterprises. One of the key challenges is the divergent understanding of risk between investors and innovators. The article emphasizes that bureaucracy and complexity of processes for obtaining financing can significantly slow down or even stop innovation initiatives, and the flexibility and adaptability of financial instruments are key to effectively supporting innovation, especially in the context of a rapidly changing market and technological progress. These results provide important insights into various aspects of innovation financing and can be used to develop more effective strategies and policies in this area.
Keywords: financial instruments; business innovations; venture capital financing; lending; crowdfunding; innovation process; startups; financial innovations